2019
DOI: 10.1007/s12671-019-01202-x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Program for Autism Spectrum Disorder: a Qualitative Study of the Experiences of Children and Parents

Abstract: Objectives Mindfulness-based programs could support children with autism spectrum disorder (ASD) and their parents to cope with autism spectrum symptoms and reduce comorbid mental health problems. In this study, we aimed to explore which change processes are involved in a mindfulness-based program for children with ASD and their parents (MYmind), according to a qualitative analysis of the families' experiences. Method Fourteen children aged 9-17 years and 31 parents (18 mothers, 11 fathers, 2 caring relatives)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 61 publications
1
24
1
Order By: Relevance
“…In general MYmind did not improve their attention systems, nonetheless trend effects point into the direction of improved orienting and executive attention. MBPs are promising and feasible for children with ASD and their parents (e.g., de Bruin et al, 2015;Ridderinkhof et al, 2018;, but this study could not strongly support the found behavioral changes with an objective test of attention.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…In general MYmind did not improve their attention systems, nonetheless trend effects point into the direction of improved orienting and executive attention. MBPs are promising and feasible for children with ASD and their parents (e.g., de Bruin et al, 2015;Ridderinkhof et al, 2018;, but this study could not strongly support the found behavioral changes with an objective test of attention.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, it could improve the capacity to disengage their attention from distressing automatic thought patterns and feelings, and thereby improve the ability to cope with stress and emotional problems. Improved social responsiveness, attention, and emotional and behavioral functioning were indeed found on parent-and self-reports after MYmind for these children with ASD (de Bruin et al, 2015;Ridderinkhof et al, 2018). However, we should be cautious to conclude that the slight improvements in orienting and executive attention are underlying these behavioral improvements.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A number of mindfulness-based treatment applications To help people in a variety of mental and emotional states, mindfulness has been used to reduce the symptoms of depression, stress, anxiety, and in the treatment of drug addiction. Programs based on Kabat Saddle models and similar models have been adopted in schools, prisons, hospitals, veterans' centers and other environments, and mindfulness programs for healthy aging, weight management, athletic performance, Helping children is used (Ridderinkhof, 2019).…”
Section: Introductionmentioning
confidence: 99%